Modeling of the Influence of Sea Ice Cycle and Langmuir Circulation on the Upper Ocean Mixed Layer Depth and Freshwater Distribution at the West Antarctic Peninsula. Issue 8 (18th August 2020) - Schultz, C.; Doney, S. C.; Zhang, W. G.; Regan, H.; Holland, P.; Meredith, M. P.; Stammerjohn, S.
Abstract: The Southern Ocean is chronically undersampled due to its remoteness, harsh environment, and sea ice cover. Ocean circulation models yield significant insight into key processes and to some extent obviate the dearth of data; however, they often underestimate surface mixed layer depth (MLD), with consequences for surface water‐column temperature, salinity, and nutrient concentration. In this study, a coupled circulation and sea ice model was implemented for the region adjacent to the West Antarctic Peninsula, a climatically sensitive region which has exhibited decadal trends towards higher ocean temperature, shorter sea ice season, and increasing glacial freshwater input, overlain by strong interannual variability. Hindcast simulations were conducted with different air‐ice drag coefficients and Langmuir circulation parameterizations to determine the impact of these factors on MLD. Including Langmuir circulation deepened the surface mixed layer, with the deepening being more pronounced in the shelf and slope regions. Optimal selection of an air‐ice drag coefficient also increased modeled MLD by similar amounts and had a larger impact in improving the reliability of the simulated MLD interannual variability. This study highlights the importance of sea ice volume and redistribution to correctly reproduce the physics of the underlying ocean, and the potential of appropriately parameterizing Langmuir circulation to help correct for biases towards shallow MLD in the Southern Ocean. The model also reproduces observed freshwater patterns in the West Antarctic Peninsula during late summer and suggests that areas of intense summertime sea ice melt can still show net annual freezing due to high sea ice formation during the winter. Key Points: Sea ice redistribution has a large impact on the mixed layer depth seasonality and interannual variability in the West Antarctic Peninsula In the West Antarctic Peninsula, areas of high summer sea ice melt can show net annual freezing due to high sea ice formation in winter Including a parameterization for Langmuir circulation based on entrainment below the mixed layer improves the simulated mixed layer depth